Service experiences in hospitals in Bangladesh: are there gender inequities? - Andaleeb, Syed Saad; Millet, Ido (© Emerald Group Publishing Limited, 2016)
This article was published in the International Journal of Health Care Quality Assurance [© Emerald Group Publishing Limited] and the definite version is available at : http://dx.doi.org/10.1108/09526861011060951 The Journal's website is at: http://www.emeraldinsight.com/doi/full/10.1108/09526861011060951